Shared-constraint approach for multi-leader multi-follower game of generation companies participating in electricity markets with carbon emission trading mechanism. (20th May 2022) - Lu, Zhilin; Liu, Mingbo; Lu, Wentian; Lin, Shunjiang
Abstract: There is a high degree of overlap between market entities covered by the carbon emission trading (CET) market and electricity market, and the two markets are closely related. Therefore, it is of great significance to analyze the impact of the CET market mechanism on the bidding strategy of generation companies (GENCOs) and electricity market clearing results. In this paper, the problem of GENCOs participating in both the day-ahead and real-time balancing electricity market within the CET mechanism is studied as a multi-leader multi-follower (MFML) Stackelberg game problem. The GENCOs are considered as leaders in the game who decide on the submitted bid and offer in terms of price and quantity to maximize their expected profit in the market, while both the clearing problems of day-ahead and real-time markets are considered as followers on the lower level. In order to expand the Nash equilibrium of the considered MFML game, the shared-constraint approach is applied to modify this problem. Two typical Nash equilibria of the proposed MLMF game are analyzed and discussed. Finally, the results of the simulations conducted on a modified IEEE 39-bus system and a real 2778-bus system indicate that GENCOs tend to submit bids with a higher price in the market under the global Nash equilibrium solution. Within the CET mechanism, the overall market clearing share of the gas-fired units increases from 21.76% to 18.1%–32.33% and 19.51%, at valley and peak loads, respectively. Thus, the operation of the CET market will make low-emission units more competitive in the electricity market. Highlights: A market framework was proposed to model interaction between CET market and electricity market. An MLMF Stackelberg game was proposed to describe strategic bidding problems of GENCOs. A shared-constraint approach was used to modify the MFML game, and two equilibria were analyzed. GENCOs tend to submit higher prices in market under the global Nash equilibrium solution. Impacts of the CET mechanism on electricity market were evaluated using a realistic case study.